Dural Ectasia in Neurofibromatosis 1: Case Series, Management, and Review. Issue 5 (27th July 2019) - Polster, Sean P; Dougherty, Mark C; Zeineddine, Hussein A; Lyne, Seán B; Smith, Heather L; MacKenzie, Cynthia; Pytel, Peter; Yang, Carina W; Tonsgard, James H; Warnke, Peter C; Frim, David M
Abstract: BACKGROUND: The natural history and management of dural ectasia in Neurofibromatosis 1 (NF1) is still largely unknown. Dural ectasias are one of the common clinical manifestations of NF1; however, the treatment options for dural ectasias remain unstudied. OBJECTIVE: To investigate the natural history, diagnosis, management, and outcome of the largest case series of patients with NF1-associated dural ectasia to date. METHODS: Records from our NF1 clinic were reviewed to identify NF1 patients with computed tomography or magnetic resonance imaging evidence of dural ectasia(s) to determine their clinical course. Demographics, symptoms, radiographic and histopathologic findings, treatment, and clinical course were assessed. RESULTS: Thirty-four of 37 patients were managed without surgery. Of the 18 initially asymptomatic patients, 5 (27.8%) progressed to symptoms attributable to a dural ectasia (onset of 2.7% per patient-year). Three patients required surgical intervention because of extraspinal mass effect. All 3 initially improved but had symptom recurrence within 2 yr. Reoperation involved shunt placement for cerebrospinal fluid (CSF) diversion. On imaging review, 26 (76.5%) of the nonsurgical patients harbored an associated nearby plexiform neurofibroma. Pathology of one surgical case revealed dural infiltration by diffuse neurofibroma. CONCLUSION: Using the largest NF1-associated dural ectasia group to date, we report the first symptom-onset rate for nonsurgical patients. In the few cases requiring surgery for decompression, primary resection, and patching of ectasias failed, subsequently requiring CSF shunting. We demonstrate imaging evidence of nearby plexiform neurofibroma in a majority of cases, which, when combined with histopathology, provides a novel explanation for the formation of dural ectasias. Graphical Abstract: